Benzodiazepine‐induced photosensitivity reactions: A compilation of cases from literature review with Naranjo causality assessment. Issue 6 (26th May 2021) - Momin, Noorulain; Phan, Phuong; Ali, Ashmal A.; I. Ali, Hamed; Seeger, Christina M.; Joseph, Merlyn
Abstract: Objective: Benzodiazepines have been reported to cause photosensitivity reactions. We characterized the clinical presentation and diagnosis of benzodiazepine‐associated photosensitivity and adjudicated these cases for a causal association with benzodiazepines. Methods: A literature search on PubMed's "MeSH" search feature and CINAHL (1964 to 2019) was performed using search terms: benzodiazepine, photosensitivity, and photosensitivity disorders/chemically induced. We applied the Naranjo scale, a standardized causality assessment algorithm, to identified cases. Results: We identified eight published cases, with 50% of patients being female with a mean age of 46.3 years. Alprazolam, tetrazepam, clobazam, and clorazepate induced phototoxic reactions. Chlordiazepoxide induced one photoallergic reaction. Photosensitivity occurred between 1‐3 days (37.5%), 7‐14 days (25%), and >14 days (25%). Photosensitivity resolved after drug discontinuation within 2 weeks (62.5%). Benzodiazepine rechallenge confirmed photosensitivity in 75% of cases. Photopatch testing was negative in two patients; however, these patients had positive oral provocation testing. However, an oral photoprovocation test, an ideal diagnostic test, was not administered to several patients. Despite these challenges, the Naranjo scale identified 5 cases as definite benzodiazepine‐induced photosensitivity. Conclusion: Five benzodiazepines induced photosensitivity reactions. Five patients showed a definite association with the Naranjo scale. Reporting to pharmacovigilance databases may help identify other benzodiazepines causing photosensitivity reactions.